Legal Inconsistency over the Blood Donor Unit and Blood Transfusion Unit Existence in Realizing Indonesia Blood Transfusion Services Authority - I Made Wirya Darma; I Gede Agus Kurniawan; Gede Eka Rusdi Antara (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2022)
This study specifically focusing on uncertainty and inconsistencies that faced on blood transfusion services caused by the existence of Blood Donor Unit and Blood Transfusion Unit led by existing norms on the statutory laws. The Act on Health, the Blood Service Government Regulation, and the Minister of Health Regulation No. 83/2014 assign blood services to the Blood Transfusion Unit. However, the existence of the Red Cross Law along with the Red Cross Government Regulation normalizes the task of providing blood services to the Blood Donor Unit, without confirming legal certainty for the Blood Transfusion Unit. This has triggered the issue of legal inconsistency towards those who carry out blood services, so a solution is needed through this study. This study is based on normative juridical legal research supported by a statutory approach as well as a legal conceptual approach. The results of this study are there are two options that can be formulated in the future, namely by basing the principle of legal preference lex posteriori derogate legi priori or based on the technique of formulating statutory norms according to the principle of clarity of formulation, certainty of the formulation of explanations, transitional provisions, closing provisions and phrases that selected in determining the executor of blood service duties.